Factors and determinants of malnutrition among under-five children in internally displaced persons (IDP) camps in Africa: a systematic review - Eucheria Ekugeni Abua; Antor Odu Ndep; Nsikakabasi Samuel George; Brian Enembe Edet; Edward Onun Okoi; Helen Lonn; Christiana Ogben; Gima Humphrey Forje; Theresa Mark Awa; Maurice-Joel Ugbe Ugbe (BMC Nutrition)
Abstract Background Internal displacement due to conflict or crises has led to millions, including children under five, residing in precarious internally displaced persons (IDP) camps. Malnutrition, predominantly undernutrition in Sub-Saharan Africa, is a significant concern in these contexts. This review aimed to assess the factors and determinants of malnutrition among under-five children in IDP Camps in Africa. Method The review was conducted according to the PRISMA guidelines, and the research protocol was registered in PROSPERO (CRD42023460266). Embase, MEDLINE, CINAHL, Web of Science, CABI Abstracts, Scopus and Google Scholar were searched methodically. The AXIS Critical Appraisal of Cross-sectional Studies Tool was utilized to evaluate the quality and risk of bias of each included study. Result After screening full-text articles, eight studies meeting eligibility criteria were included in the review. Factors influencing nutritional status of under-five children were summarized into 11 themes: Age, Gender, Caregiver’s Educational Status, Family Planning, Antenatal Care, Displacement Status, Access to Safe Water and Handwashing, Dietary Diversity, Disease History, Caregiver’s Occupation, and Household Income. Conclusion This review examined the factors contributing to malnutrition among under-five children in IDP camps in Africa, and sheds light on neglected crises. It adds to existing knowledge in this area. The findings underscore the need for future research to explore variations in malnutrition determinants across different IDP contexts and to focus on multi-sector collaboration for effective policy implementation in addressing malnutrition in African IDP camps.